2022
DOI: 10.1002/adfm.202204929
|View full text |Cite
|
Sign up to set email alerts
|

How Halogenation Impacts the Polymer Backbone Conformation: Learning from Combination of Solid‐State MAS NMR and X‐Ray Scattering

Abstract: Over the past decade, halogenated semiconducting polymers have attracted considerable interest due to their outstanding optoelectronic properties. Thus, in most of today's organic photovoltaic devices benchmark organic semiconductors are halogenated materials, either electron donor polymers or non‐fullerene acceptor (NFA) small molecules. However, the nature and position of the substituted halogen atoms in halogenated semiconducting polymers impact, through self‐assembly modification, their optoelectronic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Specifically, magnetic resonance spectroscopy (NMR and EPR) techniques allow site-specific compositions and structures in both the ordered and disordered regions of OSC materials to be identified and distinguished. , The short-range interactions at subnanometer to nanometer distances measured by these techniques also facilitate structure elucidation of OSC thin films. To this end, the emerging NMR crystallography approaches make use of the combined ssNMR, X-ray scattering, and modeling techniques, which are likely to be well-suited to characterize single-component OSCs and organic photovoltaic blends. ,− In a bottom-up strategy, it is first important to resolve the local order in single-component OSCs and then extend it to the study of complex OSC blends. Therefore, we turned our attention to systematically characterize the local order and disorder in polymeric OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, magnetic resonance spectroscopy (NMR and EPR) techniques allow site-specific compositions and structures in both the ordered and disordered regions of OSC materials to be identified and distinguished. , The short-range interactions at subnanometer to nanometer distances measured by these techniques also facilitate structure elucidation of OSC thin films. To this end, the emerging NMR crystallography approaches make use of the combined ssNMR, X-ray scattering, and modeling techniques, which are likely to be well-suited to characterize single-component OSCs and organic photovoltaic blends. ,− In a bottom-up strategy, it is first important to resolve the local order in single-component OSCs and then extend it to the study of complex OSC blends. Therefore, we turned our attention to systematically characterize the local order and disorder in polymeric OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers (CPs) are an important component of bulk-heterojunctional OPDs in which structure modification of CPs can adjust their molecular aggregation, charge transport, and optoelectronic properties. CPs possess unique semiconductor properties, and understanding how to control their optoelectronic performance is critical for designing CPs with improved photoresponse characteristics. A large number of studies in the field of organic electronics show that the halogenation strategy is an ideal method to improve the optoelectronic properties of CPs. Fluorine (F) substitution, in particular, can not only adjust the energy level structure of CPs but also improve their crystallinity, trap density, and mobility. Bai et al found that in D-A-type CPs, fluorination of electron-donating units can suppress density of trap states in the active layer, effectively enhancing performance of OPDs . Additionally, Park et al studied the effect of fluorinated alkyl chains in CPs on J dark and D* of OPDs.…”
Section: Introductionmentioning
confidence: 99%